Translating Terminology in Business Annual Reports (English-Arabic) - Al Obaidani, Khalfan S. (HERMES - Journal of Language and Communication in Business, 2018)
Business annual reports are financial statements that contain key information about a company’s activities. The reports are distributed to interested parties (e.g. stockholders, creditors, financial analysts and customers) to satisfy their information requirements. In Oman, annual business reports are produced in English and translated into Arabic in order to provide Arab readers with vital information about the companies’ operations and their financial positions. This article analyzes lexical variations, i.e. financial and business terminologies in both English and Arabic versions of the annual reports. A comparison between the English and Arabic profiles of the reports found that the business terms, e.g. ‘currents assets’, ‘asset impairment’ and ‘changes in equity’ showed less variation than others that occurred more dominantly in earlier Arabic translations. This article contributes to the discipline of Translation Studies (TS) by investigating lexical variations of business terms within sociocultural and ideological contexts in Oman. It attempts to answer the following question, ‘with respect to business and financial terms, do the Arabic versions of the annual reports reflect the notion of standardization over the course of time in specific industrial domains?’ Qualitative methods are applied to compare, describe, and analyze the textual profiles of the two versions of the reports. It concludes that the Arabic business and financial terms have become more widely established over the course of time, thus reflecting the notion of standardization. Finally, this article suggests to integrate textual analysis with sociological input to have more insight into translation agents.